Exposure, Attitudes and Proficiency Level of English among School Children in Spain - Carmen Luján-García (Calidoscópio, 2013)
This paper provides an up-to-date overview of the current role of English among Spanish young students. To that end, an analysi sof three important issues has been carried out. First, this research focuses on the different opportunities of the students to be in contact with English outside the classroom. Secondly, the attitudes of the participants have been examined using three different indicators; students’ likeability, the importance of English, and the advantages for them of knowing English. Thirdly, the participants have self-assessed their level of proficiency in English in the four different skills. The outcomes reveal that young participants have a limited contact with English, and it is basically through music, radio, books, computers and television. As regards the students’ attitudes towards English, the results prove the positive attitude of the respondents. Finally, the participants’ self-assessment of their proficiency in English is positive, though some questions that require a reflection are included in the discussion.